The Margaret Chase Smith Library: A Unique Collection Fostered by a History of Collaboration - Richards, David (Maine Policy Review, 2013)
Maine is a small state with a long history of scarce resources, of “making do,” and of “helping your neighbor.” The state’s libraries are a prime example what can be achieved to maximize resources through partnerships and collaboration. David Richards discusses the Margaret Chase Smith Library in Skowhegan, Maine, which he terms “a unique collection fostered by a history of collaboration.” Richards describes the vital role collaborations with multiple kinds of partners have played in helping the library fulfill its four functions: archives, museum, education, and public policy.